Oxford Reading Tree The Flying Carpet - Roderick Hunt; Roderick Hunt (Karachi Oxford University Press, 2025)
The stories are guaranteed to hook children into reading as they follow the characters on their magical adventures. Filled with humor, drama, detailed illustrations, and endearing characters $1! =s